Pengaruh Kepemimpinan, Komunikasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Badan Pelaksana Penyuluhan Kabupaten Sragen Dengan Motivasi Sebagai Variabel Intervening - Fathonah, Siti; Astuti, Sri (-)
The purpose of this study was to examine the influence of leadership, communication and discipline of employees working on the performance of the executing agency with motivational counseling Sragen district as an intervening variable.Keywords: leadership,communication,labr discipline,performance,motivation